Optimal timing of surgery for prenatally diagnosed choledochal cysts - Ho, In Geol; Ihn, Kyong; Jeon, Ho Jong; Lee, Dong Eun; Han, Seok Joo (Frontiers in Pediatrics, 2023)
Objective: Choledochal cysts are increasingly being diagnosed antenatally. The appropriate time of surgical treatment has the greatest impact on the prognosis of choledochal cyst treatment. The purpose of this study was to compare the clinical outcomes of prenatally diagnosed choledochal cysts in infants according to the surgical treatment timing. Methods: We retrospectively reviewed the medical records of infants who underwent surgery for choledochal cysts with antenatal diagnoses. We investigated each patient’s demographic information, type of choledochal cyst, serum liver enzyme levels, and surgical outcomes according to the surgical intervention timing. Results: Between May 2006 and December 2020, 93 infants underwent surgery to treat choledochal cysts; among them, 68 had antenatally suspected choledochal cysts. Of the 68 patients, 21 developed symptoms directly after birth. While 38 patients remained asymptomatic, 9 developed symptoms before operation. To compare surgical outcomes, asymptomatic patients were divided into early (13 cases) and late (25 cases) operation groups based on an age benchmark of 30 days. The early surgical group experienced longer times to resume a full diet (6.0±1.6 vs. 4.5±0.7, p<0.001) and longer postoperative hospital stays (11±3.9 vs. 7.5±0.8, p<0.001). Surgical complications occurred in two patients in the early operation group. Minimally invasive surgery was performed in 12 patients in the late operation group. In both groups, postoperative liver function recovered at 6 months, with no significant difference. Conclusion: The results of this study showed longer hospital stays, increased diet durations, and postoperative complications in early surgery patients. However, liver function recovery was not different between the early and late operation groups. Thus, asymptomatic patients should be closely monitored, and we recommend that definitive surgical intervention be postponed until 4 months of age or until weight reaches 7 kg.